2018
DOI: 10.1111/nmo.13318
|View full text |Cite
|
Sign up to set email alerts
|

Electro‐acupuncture at ST37 and ST25 induce different effects on colonic motility via the enteric nervous system by affecting excitatory and inhibitory neurons

Abstract: Electro-acupuncture at specific acupoints can improve intestinal motility in constipation by altering the ENS and differentially affecting excitatory and inhibitory neurons, restoring the coordination between contraction and relaxation muscles, and working in concert with the central nervous system and peripheral neural pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…When it comes to colonic motility, the situation is a bit more complicated, because the effects of acupoints located in different areas on the proximal and distal colon are inconsistent. Acupuncture at the acupoints of the forelimb (LI1–LI6 and LI11), abdomen (ST25), and back (BL25) had no significant effects on the proximal colonic motility; and acupoints of the hind paw (ST37) increased proximal colonic pressure[ 70 - 72 ]. Stimulation of the limbs (LI11, ST37, and ST36), abdomen (ST25), and back (ST37) all produced an augmented effect on distal colonic motility regardless of normal, constipated, or diarrheic state[ 73 ].…”
Section: Autonomic Nervous System Mechanism Of Acupuncturementioning
confidence: 99%
See 1 more Smart Citation
“…When it comes to colonic motility, the situation is a bit more complicated, because the effects of acupoints located in different areas on the proximal and distal colon are inconsistent. Acupuncture at the acupoints of the forelimb (LI1–LI6 and LI11), abdomen (ST25), and back (BL25) had no significant effects on the proximal colonic motility; and acupoints of the hind paw (ST37) increased proximal colonic pressure[ 70 - 72 ]. Stimulation of the limbs (LI11, ST37, and ST36), abdomen (ST25), and back (ST37) all produced an augmented effect on distal colonic motility regardless of normal, constipated, or diarrheic state[ 73 ].…”
Section: Autonomic Nervous System Mechanism Of Acupuncturementioning
confidence: 99%
“…Further results indicated the restoration of enteric neuron function by downregulating the level of nitric oxide synthase (nNOS, secreted by inhibitory neurons to induce relaxation) and upregulating the expression of choline acetyltransferase (ChAT, secreted by excitatory neurons to induce contraction). While ST25, located in the abdomen, could only downregulate the expression of nNOS; therefore, the regulatory effect of EA on enteric neurons seems to act in a region-specific manner[ 72 ] (Figure 2 ).…”
Section: Ens Mechanism Of Acupuncturementioning
confidence: 99%
“…However, much less is known on the EA mechanisms involving the enteric nervous system. In one previous study, EA was found to enhance enteric neurons 36 ; in the article published in this issue, 37 EA was found to regulate inhibitory and excitatory neurons in the enteric nervous system. More studies are needed to explore EA mechanisms involving the enteric nerves.…”
Section: Mechanis Ms Of Elec Troacupun C Turementioning
confidence: 79%
“…This implied that the relaxation and contraction function of intestinal muscles is weakened by HFD; the prolonged time for nutrient absorption enables excessive energy harvest and consequently obesity. Our results displayed that electroacupuncture can improve intestinal motility by modulating excitatory and inhibitory ENS neurons, which coordinate the contraction and relaxation muscles, and orchestrate the central nervous system and ENS [26]. Electroacupuncture treatment ameliorated the pathological ENS conditions in the obese mice by increasing ITR and modulating serum neurotransmitters.…”
Section: Discussionmentioning
confidence: 97%